Surrounded by invaders: marmoset conservation challenges in Brazilian Atlantic Forest fragments - Vanessa de Paula Guimarães-Lopes; Natasha Grosch Loureiro; Júlia Simões Damo; Fabiano Rodrigues de Melo; Flávio Henrique Guimarães Rodrigues; Rodrigo Lima Massara (Discover Conservation)
Abstract Fragmented landscapes resulting from Atlantic Forest loss can facilitate biological invasions by certain species of the Callithrix genus. These primates demonstrate high invasion potential, spreading across Brazil, competing for resources, and even hybridizing with C. aurita, the only native species to Rio Doce State Park (RDSP). Using playback for data collection and occupancy models, we investigated whether the surrounding matrix type affected Callithrix spp. occupancy probability in RDSP’s surrounding fragments. We also assessed the influence of environmental conditions and fragment size on Callithrix spp. detection probability and identified regions vulnerable to new introductions. Notably, we found no C. aurita in the fragments surrounding the park, only hybrid individuals. Furthermore, western and southern forest remnants are most susceptible to the introduction of non-native marmosets. Our findings underscore a substantial threat to RDSP’s C. aurita population and other native marmoset species of the region. We advocate for controlling allochthonous marmosets in surrounding fragments to safeguard native species.